Effect of schisanhenol on function and surface shape of rat neutrophils - ZHANG Ke-jian; LIN Tong-jun; QIN Ling; LIU Geng-tao (Acta Pharmacologica Sinica; Vol 16, No 3 (May 1995): Acta Pharmacologica Sinica, 2016)
AIM: To study the regulatory effect of Schisanhenol (Sal) on function of rat neutrophils. RESULTS: It was found that Sal (1, 10, and 100 mumol.L(-1)) inhibited neutrophil activities such as chemotaxis, phagocytosis, and superoxide anion production in vitro in a concentration-dependent manner. Changes of surface morphology of neutrophils were observed by scanning electron microscopy, showing that the ruffles and pseudopods on neutrophil surface increased under the stimulation by chemotactic peptide N-formyl-Met-Leu-Phe (FMLP). When pretreated with Sal 100 mumol.L(-1), the ruffles and pseudopods disappeared and the surface became smooth. Sal 100 mumol.L(-1) decreased the cytosolic calcium concentration of neutrophils and increased the intracellular cAMP level. CONCLUSION: These data suggested that Sal could inhibit the function of rat neutrophils through affecting the cytosolic free calcium and cAMP level besides its anti-oxidant activity.